Solidarity or National Prejudice? Migrating Brewery Workers and the Troubles with Transferring Internationalist Ideologies from the Czech Lands to the United States, 1890–1914 - Orton Alison (Jahrbuch für Wirtschaftsgeschichte, 2024)
Brewery workers who migrated between the Czech Lands and the United States existed in a complex world of fluid loyalties and ideologies that traveled with them as they crossed back and forth across the Atlantic Ocean. This article focuses on the publications of brewery workers’ unions on both sides of the ocean, as they espoused often competing and conflicting interpretations of both nationalism and internationalism. A study of these publications, which included contributions from rank-and-file union members, helps us see how migrating brewery workers and union leadership interacted with these ideologies differently according to context and location.